2015
DOI: 10.1097/eja.0000000000000319
|View full text |Cite
|
Sign up to set email alerts
|

Chronic postsurgical pain in Europe

Abstract: Clinicaltrials.gov identifier: NCT01467102.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
343
3
28

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 448 publications
(397 citation statements)
references
References 32 publications
23
343
3
28
Order By: Relevance
“…The length of pain exposure in the acute postoperative period is associated with the development of chronic postsurgical pain [40,41]. Optimal pain reduction in the acute postoperative period seems to be important, not only for fast recovery and rehabilitation in the short-term, but for the prevention of CPSP as well [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The length of pain exposure in the acute postoperative period is associated with the development of chronic postsurgical pain [40,41]. Optimal pain reduction in the acute postoperative period seems to be important, not only for fast recovery and rehabilitation in the short-term, but for the prevention of CPSP as well [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…THA is in eleventh place of the top 40 surgical procedures 1. In other studies, risk factors for chronic postsurgical pain (CPSP) were chronic preoperative pain, orthopedic surgery, and percentage of time with severe pain on day 1 after surgery 2. The quality of acute postoperative pain management is far from satisfactory,3 despite the availability of a large number of studies on techniques and medication.…”
Section: Objectivementioning
confidence: 99%
“…At 12 months, the incidence of moderate pain was 11.8% and of severe pain 2.2%. NP affected 35.4% of patients with moderate pain and 57.1% of patients with severe pain 12 . An Italian study collecting data via e-mail or telephone using BPI and DN4 and including 235 patients, has shown that the incidence of chronic postsurgical pain at 6 month was 45.2% for mild pain, 15.9% for moderate pain and 2.7% for severe pain, while the incidence of chronic post-surgical pain at 12 months was 35.9%, 11.8% and 2.5%, respectively for mild, moderate and severe pain.…”
Section: Chronic Post-surgical Painmentioning
confidence: 99%
“…The association between acute post-surgical pain intensity and further development of chronic pain was observed after breast surgery, thoracotomy and groin hernia repair, however, whether this association is an indication of the extension of neuroplasticity changes induced by surgery, by lack of adequate analgesia or by preoperative predisposing factors is still not totally explained [30][31][32] . A European study has evidenced chronic pre-surgical pain, orthopedic surgery and percentage of time with severe pain in the first post-surgical day as risk factors for chronic post-surgical pain 12 . An Italian study has also evidenced that severe pain during the first 24 post-surgical hours seems to be predictor of chronic post-surgical pain 13 .…”
Section: Pathophysiology Of Neuropathic Pain After Peripheral Nerve Imentioning
confidence: 99%